MSME Strategy the Impact of Financial Literacy,Self-Efficacy,and Financial Attitudes in improving MSME Business Performance in Indonesia - Erna Retno Rahadjeng; Imam Mukhlis; Danardana Murwani; Iva Khoiril Mala (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is still said to be minimal for the process of managing business performance. It is proven that financial management is still inconsistent and even not according to plan. The purpose of this study looks at the strategies used by MSME actors to improve their business performance through the finance department by involving sharing factors that fall into the category of financial system management. Judging from the factors of financial literacy, self-efficacy and financial attitude. This type of research uses bibliometric analysis. The results of the analysis looked at many MSME strategies in the financial system, researchers found that there were factors that had not been widely associated with financial attitudes. It was found that the existence of a financial attitude on business performance can shape knowledge and foster self-confidence to be able to provide financial system plans both from the past and the future. With the understanding and adjustment of the situation, it makes the financial system efficient and stable.